2014
DOI: 10.1371/journal.pone.0115229
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and Neonatal Brain Microstructure in Term Born Infants: A Birth Cohort Study

Abstract: ObjectiveUnderstanding healthy brain development in utero is crucial in order to detect abnormal developmental trajectories due to developmental disorders. However, in most studies neuroimaging was done after a significant postnatal period, and in those studies that performed neuroimaging on fetuses, the quality of data has been affected due to complications of scanning during pregnancy. To understand healthy brain development between 37–41 weeks of gestational age, our study assessed the in utero growth of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…To our knowledge, there is only 1 other published study focused on white matter microstructural development in term infants at young postnatal ages similar to those in our study. 20 In that study, a positive correlation with gestational age was found in several white matter regions for FA values. Analyses on diffusivities were not available.…”
Section: Figmentioning
confidence: 67%
See 1 more Smart Citation
“…To our knowledge, there is only 1 other published study focused on white matter microstructural development in term infants at young postnatal ages similar to those in our study. 20 In that study, a positive correlation with gestational age was found in several white matter regions for FA values. Analyses on diffusivities were not available.…”
Section: Figmentioning
confidence: 67%
“…In each week of gestation and/or week of life during the term period, white matter continues to mature in patterns of posterior to anterior and central to peripheral. 18 A few studies have evaluated white matter microstructures in relation to term gestational ages 19,20 ; nevertheless, studies including white matter imaging data for term-born infants have mostly focused on the comparison to preterm, 20,21 but not on the trajectory of white matter development in term-born infants during the normal term period. Nor is it clear whether gestational lengths at birth of termborn infants impact this trajectory and longer-term development into childhood.…”
mentioning
confidence: 99%
“…Preterm infants at term age showed reduced anisotropy in the internal capsule compared to infants born at term (Dudink et al 2007, Hüppi et al 2001, Pogribna et al 2013, Rose et al 2009). It was recently shown that even in the normal range of gestation (37 to ~41 weeks), FA in the anterior limb of the internal capsule changes as a function of gestational age (Broekman et al 2014). Anisotropy in the posterior limb of the internal capsule was found to be reduced in a group of 11-year-olds with a history of preterm birth (Nagy et al 2003), suggesting persistence of prematurity-related white matter abnormalities into late life.…”
Section: Diffusion Tensor Imaging Applications In Infant Researchmentioning
confidence: 99%
“…Of particular interest is whether extrauterine brain development in the preterm neonate significantly deviates from a term-born neonate [Lefèvre et al, 2015]. Previous diffusion imaging studies of preterm WM and GM microstructure have demonstrated less mature networks and tissues at term-equivalent age, which was correlated with gestational age at birth [Ball et al, 2013;Broekman et al, 2014;Pannek et al, 2013]. For example, Pannek et al (2013) showed reduced FA in a frontal lobe network at term-equivalent age and our results show rapid areal expansion in similar regions in both GM and WM, especially between 32 and 36 PMW for WM.…”
Section: Comparison To Imaging Studiesmentioning
confidence: 99%